Analisis Lirik Lagu dan Aplikasinya dalam Pembelajaran Gaya Bahasa serta Puisi di Sekolah Dasar - Fauzi Rahman; Puji Anto (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2015)
This paper describes how the lyrics can be positioned as a poetry which can be applied by teachers in schools as a learning media of Indonesian language. The lyrics are sung poetry. This statement is the foundation that teachers can make the lyrics of famous songs as teaching material of language style and poetry in school. In this paper taken an example lyrics to a song called